Design of planning model for ERP system in warehouse management: an empirical study of public hospital in Indonesia. Issue 1 (December 2020) - Utami, F D; Puspitasari, W; Saputra, M
Abstract: Public Hospital is one of the complicated information in the healthcare industry. ERP provides a concept that integrates a whole series of business processes, so they are mutually sustainable as part of business management to achieve the goals of an organization. In line with the hospital's information system, ERP provides a solution for managing data information that runs in hospitals. As one of District Government Hospitals in Indonesia that provide health services, RSUD XYZ does not have an independent information system that manages the hospital's vital data specifically in warehouse management yet. Procurement and management of goods on a regular basis without a system managing in terms of inventory bring through redundancy, ineffective, and inefficient management of data in the warehouse. This research focuses on the planning model system for the public hospital in inventory management business processes, developed using OpenERP at Inventory Management module and QuickStart method. The results of this study is a design of a planning model for inventory management system in the public hospital. This research explains how the ERP system can help improve health services in the public hospital under business processes that should be in the healthcare industry.